Peran Orang Tua terhadap Pencegahan Stunting pada Anak Usia Dini melalui Perbaikan Pola Makan dan Lingkungan - Fattikasary, Ayva Tuzqya; Jayadinata, Asep Kurnia; Ardiyanti, Dhea; Shofuroh, Hanifa; Muqodas, Idat; Rini, Khansa Pramesti Sulistyo; Fadillah, Khoerunnisa Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting is a complex problem that is influenced by various factors. This research aims to understand the challenges in stunting prevention in the Pangalengan area and explore potential solutions. Through a qualitative case study, this research found that lack of parental knowledge, limited access to nutritious food, and poor environmental conditions are the main challenges. Community-based interventions, such as workshops and mentoring, can be an effective solution. However, stronger policy support is needed to address the issue as a whole. This study concludes that stunting prevention requires a multisectoral and sustainable approach.